2003
DOI: 10.1046/j.1365-2222.2003.01564.x
|View full text |Cite
|
Sign up to set email alerts
|

Hymenoptera ultra‐rush venom immunotherapy (210 min): a safety study and risk factors

Abstract: Treatment with honeybee extract induced more SR than the treatment with yellow jacket and wasp venom. Doses increase phase on day 1 is risk factors for SR of ultra-RVIT, as well as the severity of the prior reaction. Age, degree of positive skin tests, and specific IgE are not risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
74
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 28 publications
7
74
1
6
Order By: Relevance
“…As a result, we did not identify any of the significant risk factors proposed by other authors [14,16,22]. No significant differences were found for the species responsible (P=.45), although 6 of the 10 patients with systemic reactions were receiving immunotherapy with bee venom.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…As a result, we did not identify any of the significant risk factors proposed by other authors [14,16,22]. No significant differences were found for the species responsible (P=.45), although 6 of the 10 patients with systemic reactions were receiving immunotherapy with bee venom.…”
Section: Discussioncontrasting
confidence: 68%
“…Standard protocols (lasting 8-15 weeks), rush protocols (4-7 days), and ultrarush protocols (1-2 days) can all be used. Ultrarush protocols have been shown to be safe [9,12,[15][16][17]; however, other prospective studies have shown a rapid increase in dose to be an independent risk factor for adverse systemic reactions [13,18]. In the case of ultrarush protocols, this risk is increased 1.8-fold, although the protocols are costeffective [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the safety and efficacy of this treatment is controversially discussed. Data concerning its use in children are very scarce.Adverse systemic reactions under ultra-rush immunotherapy for more than 210 minutes were described by Birnbaum et al [3]. The reactions were mainly those on the skin, such as urticaria, and/or angioedema.…”
mentioning
confidence: 96%
“…The ultra-rush procedure is the briefest one for initiation of VIT and was first described by Zwan et al [12]. It has been used frequently in the last few years, especially in adult patients with insect venom allergy [2,3,13,14]. However, the safety and efficacy of this treatment is controversially discussed.…”
mentioning
confidence: 99%
See 1 more Smart Citation